Applying a Community Violence Framework to Understand the Impact of Immigration Enforcement Threat on Latino Children. Issue 3 (25th September 2018) - Barajas‐Gonzalez, R. Gabriela; Ayón, Cecilia; Torres, Franco
Abstract: Heeding the call put out by the New England Journal of Medicine (2017), we utilize an ecological–transactional model as a conceptual framework for understanding existing literature and for guiding future research on immigration enforcement threat and Latino child development. Using the World Health Organization's definition of violence, we draw on literature from psychology, medicine, social work, and developmental psychology to outline how the anti‐immigrant climate in the United States and the threat of immigration enforcement practices in everyday spaces are experienced by some Latino children as psychological violence. Researchers, teachers, and practitioners are encouraged to be aware of how uncertainty and threat regarding familial safety adversely impacts the lives of Latino children in immigrant households, especially in charged, anti‐immigrant climates. Abstract : Read the accompanying policy brief from SRCD